Forming Religious Character Through Habit: Inclusive Islamic Education for Students with Special Needs in a Special School Context - Kusuma Wardhani, Maharani; Khadavi, M. Jadid (HEUTAGOGIA: Journal of Islamic Education, 2025)
This study investigates the implementation of Islamic Religious Education (PAI) for students with special needs at SLB Sinar Harapan 2 Probolinggo, focusing on teaching methods, instructional strategies, challenges, and the impact on character development. Employing a qualitative case study approach, the research involved fifteen purposively selected participants, including teachers, administrators, and parents, with data gathered through classroom observations, semi-structured interviews, and institutional document analysis. Findings indicate that adaptive and multisensory teaching methods—such as visual aids, sign language, tactile media, and structured religious routines—were integral in supporting student engagement and understanding. Teachers utilized routine-based strategies, collaborative family involvement, and differentiated instruction aligned with Individualized Education Programs (IEPs). Despite challenges including limited instructional time, communication barriers, and inadequate resources, the study found that PAI learning contributed positively to students’ religious behavior, independence, empathy, and participation in communal rituals. Additionally, parental engagement increased during religious events, reinforcing school-based learning at home. These results highlight the potential of inclusive religious education to foster moral and spiritual development among students with diverse disabilities. The study underscores the importance of teacher adaptability, institutional support, and culturally grounded pedagogy in advancing inclusive Islamic education. Limitations include the single-school focus and lack of direct student voice. Future research should explore broader contexts, assess long-term outcomes, and incorporate student perspectives. The findings offer practical implications for educators, policymakers, and curriculum designers committed to equitable religious education for all learners.